The EURO-D Measure of Depressive Symptoms in the Aging Population: Comparability Across European Countries and Israel - Maskileyson, Dina; Seddig, Daniel; Davidov, Eldad (Frontiers in Political Science, 2021)
Most of the countries in Europe are experiencing a rapid aging of their populations and with this an increase in mental health challenges due to aging. Comparative research may help countries to assess the promotion of healthy aging in general, and mentally healthy aging in particular, and explore ways for adapting mental health policy measures. However, the comparative study of mental health indicators requires that the groups understand the survey questions inquiring about their mental health in the same way and display similar response patterns. Otherwise, observed differences in perceived mental health may not reﬂect true differences but rather cultural bias in the health measures. To date, research on cross-country equivalence of depression measures among older populations has received very limited attention. Thus, there is a growing need for the cross-country validation of existing depression measures using samples of the older population and establishing measurement equivalence of the assessment tools. Indeed, insights on mental health outcomes and how they compare across societies is paramount to inform policy makers seeking to improve mental health conditions of the populations. This study, therefore, aims to examine measurement equivalence of self-reported depressive symptoms among older populations in 17 European countries and Israel. The data for the current analysis are from the sixth wave (2015) of the Survey on Health, Ageing and Retirement in Europe (SHARE) and consist of the population of respondents 50 years of age and older. The measurement of depression is based on the EURO-D scale, which was developed by a European consortium. It identifies existing depressive symptoms and consists of the 12 items: depression, pessimism, suicidality, guilt, sleep, interest, irritability, appetite, fatigue, concentration, enjoyment, and tearfulness. We examine the cross-country comparability of these data by testing for measurement equivalence using multigroup confirmatory factor analysis (MGCFA) and alignment. Our findings reveal partial equivalence thus allowing us to draw meaningful conclusions on similarities and differences among the older population across 18 countries on the EURO-D measure of depression. Findings are discussed in light of policy implications for universal access to mental health care across countries.